Maternity staff perspectives regarding resource demands of breastfeeding supportive practices in accordance with the Baby‐Friendly Hospital Initiative accreditation: a Q methodology approach. (22nd February 2016) - Huang, Chiu‐Mieh; Hung, Wei‐Shu; Lai, Jung‐Nien; Kao, Yu‐Hsiu; Wang, Ching‐Ling; Guo, Jong‐Long
Abstract: Aim: To explore the resource demands of implementing the Baby‐Friendly Hospital Initiative among maternity staff. Background: Implementing the Baby‐Friendly Hospital Initiative is the most recognized global strategy for ensuring that hospital routines support breastfeeding. The maternity services of Baby‐Friendly Hospital Initiative accredited hospitals are evaluated according to the Ten Steps to Successful Breastfeeding. Design: Q methodology was applied to investigate the perspectives of 60 maternity staff in Northern Taiwan. Methods: Data were collected from May ‐ December 2014. An online Q‐sort platform was designed for the participants to perform sorting. The Q‐sorts were subjected to factor analysis by using PQ Method software. Factors were extracted using principal component analysis with a varimax rotation. A combination of eigenvalues and a scree plot were employed to determine the number of retained factors. Results: Four factors retained in the final model accounted for 56% of the total variance: (1) emphasis on implementing an institutional policy; (2) emphasis on providing supportive practices for breastfeeding mothers; (3) emphasis on establishing continual breastfeeding support; and (4) emphasis on managing breastfeeding supportive practices concerning a designated time period. The participants that were associated with Factors 1 and 3 emphasized the necessity of allocating resources to Steps 1, 2 and 10 of the Ten Steps. The participants associated with Factors 2 and 4 emphasized allocating resources to Steps 2–5 and 7. Conclusions: This study revealed the various perspectives of maternity staff regarding the resource demands of implementing the Baby‐Friendly Hospital Initiative. These perspectives may serve as a reference for decision‐makers in prioritizing resource allocation.